The Effect of Omega 3 and Vitamin E against Avian Influenza in Broiler Chickens - TASEER, M.; ASLAM, A.; CHAUDHARY, Z. I.; ASHRAF, K.; AKHTAR, R.; MUSTAFA, G. (Journal of the Hellenic Veterinary Medical Society, 2018)
The present study assessed the individual and combined effect of vitamin E and omega 3 against low pathogenic avian influenza (LPAI) virus in broiler birds. Day-old broiler birds (n=125) were equally divided into five groups (A, B, C, D & E). Group A was non infected negative control. While groups B, C, D and E were infected with low pathogenic avian influenza (H9N2) virus at 28th day (2 HAunits/bird). Group B was given omega 3 at rate of 150mg/kg in feed. Group C was given vitamin E 200 IU/kg. Group D was offered vitamin E and omega 3. Group E was designated as positive control without supplementation. The results revealed significantly increased antibody titer, decreased heterophil lymphocyte ratio, improved feed conversion ratio and least histopathological lesions in birds given vitamin E alone followed by the group given combination of vitamin E and omega 3. These results concluded the positive impact of Vitamin E as compare to omega 3 alone and combined omega 3 with vitamin E against LPAI infection in broiler chickens. These findings can have useful field application in control of avian influenza.